Evaluation of [18F]AlF-EMP-105 for Molecular Imaging of C-Met - Jin Hui Teh; Ala Amgheib; Ruisi Fu; Chris Barnes; Joel Abrahams; Ali Ashek; Ning Wang; Zixuan Yang; Muneera Mansoorudeen; Nicholas J. Long; Eric O. Aboagye (MDPI AG, 2023)
C-Met is a receptor tyrosine kinase that is overexpressed in a range of different cancer types, and has been identified as a potential biomarker for cancer imaging and therapy. Previously, a 68Ga-labelled peptide, [68Ga]Ga-EMP-100, has shown promise for imaging c-Met in renal cell carcinoma in humans. Herein, we report the synthesis and preliminary biological evaluation of an [18F]AlF-labelled analogue, [18F]AlF-EMP-105, for c-Met imaging by positron emission tomography. EMP-105 was radiolabelled using the aluminium-[18F]fluoride method with 46 ± 2% RCY and >95% RCP in 35-40 min. In vitro evaluation showed that [18F]AlF-EMP-105 has a high specificity for c-Met-expressing cells. Radioactive metabolite analysis at 5 and 30 min post-injection revealed that [18F]AlF-EMP-105 has good blood stability, but undergoes transformation-transchelation, defluorination or demetallation-in the liver and kidneys. PET imaging in non-tumour-bearing mice showed high radioactive accumulation in the kidneys, bladder and urine, demonstrating that the tracer is cleared predominantly as [18F]fluoride by the renal system. With its high specificity for c-Met expressing cells, [18F]AlF-EMP-105 shows promise as a potential diagnostic tool for imaging cancer.